Influence of nitrate supplementation on endurance cyclic sports performance: A systematic review - Calvo, J. L.; Alorda-Capo, F.; Pareja-Galeano, H.; Jiménez, S. L. (Nutrients, 2020)
Endurance can be defined as the capacity to maintain one`s velocity or power output for the longest possible time. Maintaining such activity can lead to the onset of fatigue. Dietary nitrate supplementation produces an ergogenic effect due to the improvement of mitochondrial oxygen efficiency through a reduction in the oxygen cost of exercise that increases vasodilation and blood flow to the skeletal muscle in recreationally active subjects. However, the effects of dietary nitrate supplementation on well-trained endurance athletes remain unclear; such supplementation could affect more performance areas. In the present study, a systematic review of the literature was conducted to clarify the use and effects of nitrate as a dietary supplement in endurance athletes trained in cyclic sports (repetitive movement sports). A systematic search was carried out following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines in the databases of SCOPUS, Web of Science (WOS), Medline (PubMed), and Sport Discus from 1 January 2010 to 30 November 2019. Twenty-seven studies were included in the study. The methodological quality of the articles was assessed using the McMaster Critical Review Form. Statistically significant ergogenic results were obtained in 8 (29.63%) of the 27 studies investigated, with significant results obtained for cardiorespiratory parameters and performance measures. Improvement in exercise tolerance was obtained, which could help with exhaustion over time, while the improvement in exercise economics was not as clear. Additionally, the dose necessary for this ergogenic effect seems to have a direct relationship with the physical condition of the athlete. The acute dose is around 6-12.4 mmol/day of nitrate administered 2-3 h before the activity, with the same amount given as a chronic dose over 6-15 days. Further studies are required to understand the factors that affect the potential ergogenic impacts of nitrate on athletic performance among endurance athletes.